Development of highly radiopure NaI(Tl) scintillator for PICOLON dark matter search project. (16th February 2021) - Fushimi, K; Kanemitsu, Y; Hirata, S; Chernyak, D; Hazama, R; Ikeda, H; Imagawa, K; Ishiura, H; Ito, H; Kisimoto, T; Kozlov, A; Takemoto, Y; et al.
Abstract: Highly radiopure NaI(Tl) was developed to search for particle candidates of dark matter. Optimized methods were combined to reduce various radioactive impurities. $^{40}$ K was effectively reduced by the recrystallization method. The progenies of the decay chains of uranium and thorium were reduced by appropriate resins. The concentration of natural potassium in NaI(Tl) crystal was reduced to 20 ppb. Concentrations of alpha-ray emitters were successfully reduced by appropriate resin selection. The present concentrations of the thorium series and $^{226}$ Ra were $1.2±1.4$ $μ$ Bq/kg and $13±4$ $μ$ Bq/kg, respectively. No significant excess in the concentration of $^{210}$ Pb was obtained, and the upper limit was 5.7 $μ$ Bq/kg at 90$#$ CL. The achieved level of radiopurity of NaI(Tl) crystals makes the construction of a dark matter detector possible.